2018
DOI: 10.1371/journal.pone.0195814
|View full text |Cite
|
Sign up to set email alerts
|

In situ observations of coral bleaching in the central Saudi Arabian Red Sea during the 2015/2016 global coral bleaching event

Abstract: Coral bleaching continues to be one of the most devastating and immediate impacts of climate change on coral reef ecosystems worldwide. In 2015, a major bleaching event was declared as the “3rd global coral bleaching event” by the United States National Oceanic and Atmospheric Administration, impacting a large number of reefs in every major ocean. The Red Sea was no exception, and we present herein in situ observations of the status of coral reefs in the central Saudi Arabian Red Sea from September 2015, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
121
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(136 citation statements)
references
References 50 publications
(88 reference statements)
13
121
1
1
Order By: Relevance
“…Yet again the corals in this study showed no evidence of reduced growth or trace element disruption during that year, with only a minor disruption of some trace elements in 2009. Similarly, in 2015/2016 when bleaching was also reported in the region (Monroe et al, 2018), the site-specific DHWs were 0.1°C weeks while the Coral Reef Watch station suggests >10°C weeks. Alternatively, it could have been a combination of the strength and duration of the 1997-2001 ENSO event that caused the noticeable disruption in calcification and trace element incorporation that was not replicated during the milder 2010 La Niña event.…”
Section: 1029/2019gc008312mentioning
confidence: 80%
See 2 more Smart Citations
“…Yet again the corals in this study showed no evidence of reduced growth or trace element disruption during that year, with only a minor disruption of some trace elements in 2009. Similarly, in 2015/2016 when bleaching was also reported in the region (Monroe et al, 2018), the site-specific DHWs were 0.1°C weeks while the Coral Reef Watch station suggests >10°C weeks. Alternatively, it could have been a combination of the strength and duration of the 1997-2001 ENSO event that caused the noticeable disruption in calcification and trace element incorporation that was not replicated during the milder 2010 La Niña event.…”
Section: 1029/2019gc008312mentioning
confidence: 80%
“…Given that widespread bleaching and mortality is likely to occur at around eight DHWs (G. Liu et al, 2013), this created a thermally stressful environment for shallow-water corals, which periodically experienced temperatures that were > 1°C above the MMM (Figure 2). In addition to the episodic El Niño related events, the Red Sea's average SST is increasing at a faster rate than most tropical regions, with models forecasting a 2 to 3°C SST rise in the central Red Sea by the end of the 21st century (Cantin et al, 2010;Monroe et al, 2018;Stocker et al, 2013). In addition to the episodic El Niño related events, the Red Sea's average SST is increasing at a faster rate than most tropical regions, with models forecasting a 2 to 3°C SST rise in the central Red Sea by the end of the 21st century (Cantin et al, 2010;Monroe et al, 2018;Stocker et al, 2013).…”
Section: Site Description and Climatologymentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, a strong event occurred during the 2015 El Niño (Figure S9), which could be the same as the one that caused bleaching in the nearby Al Lith region (Figure ). Although details have yet to be published, bleaching has been reported near Farasan (Monroe et al, ). We have also observed MHWs of high intensity over the northern NRS, and some bleaching was confirmed at Ras Qisbah (eastern northernmost coast) in 2006 (Bruckner & Dempsey, ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides their role as fundamental reef builders, Porites corals are also among the most resistant corals to increasing water temperatures (LaJeunesse et al, ). During both the 2010 and the 2016 bleaching events, Porites was among the least‐affected coral genera in the Red Sea, with less than 40% of the resident population showing signs of bleaching (Furby, Bouwmeester, & Berumen, ; Monroe et al, ).…”
Section: Introductionmentioning
confidence: 99%